Abnormalities in Cortical GABAergic Interneurons of the Primary Motor Cortex Caused by Lis1 (Pafah1b1) Mutation Produce a Non-drastic Functional Phenotype - Domínguez-Sala, E.; Valdés-Sánchez, L.; Canals, S.; Reiner, O.; Pombero, A.; García-López, R.; Estirado, A.; Pastor, D.; Geijo-Barrientos, E.; Martínez, S. (Frontiers in Cell and Developmental Biology, 2022)
LIS1 (PAFAH1B1) plays a major role in the developing cerebral cortex, and haploinsufficient mutations cause human lissencephaly type 1. We have studied morphological and functional properties of the cerebral cortex of mutant mice harboring a deletion in the first exon of the mouse Lis1 (Pafah1b1) gene, which encodes for the LisH domain. The Lis1/sLis1 animals had an overall unaltered cortical structure but showed an abnormal distribution of cortical GABAergic interneurons (those expressing calbindin, calretinin, or parvalbumin), which mainly accumulated in the deep neocortical layers. Interestingly, the study of the oscillatory activity revealed an apparent inability of the cortical circuits to produce correct activity patterns. Moreover, the fast spiking (FS) inhibitory GABAergic interneurons exhibited several abnormalities regarding the size of the action potentials, the threshold for spike firing, the time course of the action potential after-hyperpolarization (AHP), the firing frequency, and the frequency and peak amplitude of spontaneous excitatory postsynaptic currents (sEPSC's). These morphological and functional alterations in the cortical inhibitory system characterize the Lis1/sLis1 mouse as a model of mild lissencephaly, showing a phenotype less drastic than the typical phenotype attributed to classical lissencephaly. Therefore, the results described in the present manuscript corroborate the idea that mutations in some regions of the Lis1 gene can produce phenotypes more similar to those typically described in schizophrenic and autistic patients and animal models.